PENGARUH PEMBERIAN REWARD TERHADAP MOTIVASI BELAJAR SISWA KELAS V SDN 198 CINENNUNG KECAMATAN CINA KABUPATEN BONE - Sudirman Sudirman; Kasmawati Kasmawati; Sitti Jauhar Sitti Jauhar (Bestari: Jurnal Pendidikan dan Kebudayaan, 2023)
This research is a quantitative pre-experimental study that aims to describe the learning motivation of fifth-grade students at SDN 198 Cinennung, Cina District, Bone Regency, and the effect of giving rewards on the learning motivation of fifth-grade students at SDN 198 Cinennung, Cina District, Bone Regency. The variables in this study are reward (independent variable) and student learning motivation (dependent variable). The population in this study were fifth-grade students at SDN 198 Cinennung totaling 34 students. The sampling technique in this study used non-probability sampling in the form of saturated sampling—research data obtained by distributing questionnaires describing student motivation and documentation. Data collection techniques were used to pretest and posttest. The data analysis technique was descriptive and inferential analysis using the One Group Pretest Posttest Design. The results obtained in this study were: (1) There was a difference in the learning motivation of fifth-grade students at SDN 198 Cinennung before and after giving rewards, (2) There was a significant effect of giving rewards on the learning motivation of fifth-grade students at SDN 198 Cinenung.